Development of a subunit vaccine containing recombinant Riemerella anatipestifer outer membrane protein A and CpG ODN adjuvant. Issue 1 (1st January 2015) - Chu, Chun-Yen; Liu, Chia-Hui; Liou, Jhong-Jie; Lee, Jai-Wei; Cheng, Li-Ting
Highlights: OmpA was combined with CpG ODN plasmids as a vaccine against R. anatipestifer . CpG ODN enhanced IFN-γ, IL-12 and IL-6 production by duck PBMC. CpG ODN helped increase antigen-specific lymphocyte population and T cell activation. OmpA + CpG ODN reduced pathological lesions by 90% in a challenge experiment. Abstract: Riemerella anatipestifer, a Gram-negative bacillus, causes septicemia that can result in high mortality for ducklings. In this study, we evaluated the immune response and protective efficacy provided by a subunit vaccine containing recombinant outer membrane protein A (rOmpA) and plasmid constructs containing CpG oligodeoxynucleotides (ODN). Results showed that CpG ODN enhanced both humoral and cell-mediated immunity elicited by rOmpA as early as two weeks after primary immunization. When compared to ducks immunized with rOmpA, ducks immunized with rOmpA + CpG ODN showed higher levels ( p < 0.05) of antibody titer, T cell proliferation, and percentages of CD4 + and CD8 + T cell in peripheral blood mononuclear cells (PBMCs). The relative fold inductions of mRNA expression of Th1-type (IFN-γ and IL-12), and Th2-type (IL-6) cytokines in PBMCs isolated from ducks immunized with rOmpA + CpG ODN were significantly higher than those of the rOmpA group. Homologous challenge result showed that the rOmpA + CpG ODN vaccine reduced the pathological score by 90% in comparison with the saline control. In conclusion, our study found that CpG ODN can enhance both humoral and cellular immunity elicited by a rOmpA vaccine. The rOmpA + CpG ODN vaccine can be further developed as a subunit vaccine against R. anatipestifer .